Detection of Equatorial Plasma Velocity Modulations Associated With Planetary Period Oscillations in Saturn's Magnetosphere. Issue 5 (3rd May 2022) - Bradley, T. J.; Provan, G.; Cowley, S. W. H.; Wilson, R. J.
Abstract: We analyze a database of 8920 measurements of thermal ion vector velocities obtained by the Cassini CAPS/IMS instrument in the near‐equatorial (±10° latitude) region of Saturn's magnetosphere in the radial range of 5.5–21.5 Saturn radii ( R S ) for the presence of modulations due to planetary period oscillations (PPOs). The data span 2004–2012, from Saturn late southern summer to early northern spring, and are analyzed using PPO phases derived previously from Cassini magnetic field data. For the near‐equinox and northern spring data 2008–2012 we show that both northern and southern PPO modulations are present in the azimuthal velocity component with similar amplitudes, typically ∼3 ± 1.5 km s −1 in the inner part of the system inside ∼10–12 R S, rising to typically ∼9 ± 3.5 km s −1 in the outer part of the system to ∼20 R S . Oscillation phases are overall consistent with expectations for PPO modulations driven from the corresponding polar ionospheres in both cases. For the late southern summer data 2004–2007, southern PPO modulations are also present with similar properties, but no clear northern modulations were detected, indicating weaker amplitudes in this case. These findings mirror similar properties in the amplitudes of magnetic field PPO oscillations observed in previous studies. Our results constitute the first direct detection of PPO‐related velocity modulations in Saturn's magnetospheric plasma. However, no clear PPO effects were found in either the radial or colatitudinal velocities, indicating weaker modulations, if any, in these components. Key Points: We analyze a database of Cassini Saturn equatorial ion velocities 2004–2012 spanning 5.5–21.5 R S for planetary period oscillations (PPOs) Northern and southern PPOs are detected at amplitudes few to ∼10 km s –1 in the azimuthal but not in the radial or colatitudinal components Azimuthal flow phases are consistent with expectations for oscillations driven outward from the corresponding polar ionospheres